Assessing the Feasibility of Vertical Greening Systems for Air Pollution Mitigation in Lisbon: A GIS Approach to Identifying Suitable Buildings - Boieiro, Francisco Salgueiro Maltez Matos (2024)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies